An All‐Inorganic Colloidal Nanocrystal Flexible Polarizer. Issue 26 (21st May 2019) - Zhang, Simin; Shi, Wenxiong; Siegler, Timothy D.; Gao, Xiaoqing; Ge, Feng; Korgel, Brian A.; He, Yan; Li, Shuzhou; Wang, Xun
Abstract: Inorganic single crystals with anisotropic structures usually suffer from high brittleness and stiffness. Flexible polymers are used to replace inorganic crystals, but the hot‐stretching‐induced orientation process is tedious, and oriented molecular chains tend to revert to random coils during aging. To overcome these obstacles and using the similarities between sub‐1 nm nanowires (NWs) and linear polymers, we successfully fabricated anisotropic, transparent, flexible, and stable (ATFS) NW films with great potential for optical applications through a wet‐spinning method. The NW films show birefringence, and their birefractive index is higher than that of many polymers. They also showed polarized absorption of UV light and anisotropic scattering of visible light. The integrated films composed of NWs and quantum dots showed good fluorescence polarization. The tedious synthesis of quantum rods and fabrication of oriented polymer films can thus be avoided. Abstract : A strong likeness : Inorganic sub‐1 nm nanowires (NWs) are similar to linear polymers from a dimension viewpoint. By using sub‐1 nm GdOOH nanowires as building blocks, thin films with anisotropic, transparent, flexible and stable (ATFS) features showing great potential for optical applications were fabricated.